2002
DOI: 10.1152/physiolgenomics.00030.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of theRf-1region from FHH onto the ACI background increases susceptibility to renal impairment

Abstract: The genetically hypertensive fawn-hooded (FHH/Eur) rat is characterized by the early presence of systolic and glomerular hypertension, progressive proteinuria (UPV), and albuminuria (UAV), and focal glomerulosclerosis, resulting in premature death from renal failure. Previous studies showed that at least five genetic loci (Rf-1 to Rf-5) were linked to the development of renal impairment. Of these five, Rf-1 appears to play a major role. To study the impact of Rf-1 in the absence of the other loci, we transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
1
30
2
Order By: Relevance
“…To enhance renal damage susceptibility, that is, albuminuria/proteinuria and focal glomerulosclerosis, in the resistant ACI background, however, animals were subjected to either unilateral nephrectomy (Nx) or NO inhibition by treatment with L-NAME or a combination of both procedures. [92][93][94][95][96] By using this protocol, different segments of the FHH-Rf-1 region in five subcongenic ACI strains directly aggravated indeed the susceptibility of kidney damage and the autoregulation in congenic rats (Table 2). [92][93][94][95][96] Thus, the Rf-1 locus contains at least one gene that might influence the susceptibility to progressive renal failure in the presence of higher BP values due to NO inhibition or Nx.…”
Section: Loc501853mentioning
confidence: 99%
See 2 more Smart Citations
“…To enhance renal damage susceptibility, that is, albuminuria/proteinuria and focal glomerulosclerosis, in the resistant ACI background, however, animals were subjected to either unilateral nephrectomy (Nx) or NO inhibition by treatment with L-NAME or a combination of both procedures. [92][93][94][95][96] By using this protocol, different segments of the FHH-Rf-1 region in five subcongenic ACI strains directly aggravated indeed the susceptibility of kidney damage and the autoregulation in congenic rats (Table 2). [92][93][94][95][96] Thus, the Rf-1 locus contains at least one gene that might influence the susceptibility to progressive renal failure in the presence of higher BP values due to NO inhibition or Nx.…”
Section: Loc501853mentioning
confidence: 99%
“…[92][93][94][95][96] By using this protocol, different segments of the FHH-Rf-1 region in five subcongenic ACI strains directly aggravated indeed the susceptibility of kidney damage and the autoregulation in congenic rats (Table 2). [92][93][94][95][96] Thus, the Rf-1 locus contains at least one gene that might influence the susceptibility to progressive renal failure in the presence of higher BP values due to NO inhibition or Nx. 92 Van Dijk et al 93,95,96 demonstrated in a congenic Rf-3 strain a slightly increased susceptibility to renal damage (Table 2), while single Rf-4 and Rf-5 congenics appeared normal in comparison with ACI, respectively.…”
Section: Loc501853mentioning
confidence: 99%
See 1 more Smart Citation
“…Congenic animals were developed by marker-assisted selective breeding of FHH and BN rats as reported previously (25). Sequencing of positional candidate genes was performed using genomic DNA and cDNA on an ABI3730 capillary sequencer according to the manufacturer's suggested protocol.…”
Section: Generation Of Congenic Animals and Sequencing Of Candidate Gmentioning
confidence: 99%
“…For example, the risk of development of end-stage renal disease is greater in black, compared with non-black, hypertensive patients (23, 25). Recent evidence from animal models of hypertension supports a genetic basis for susceptibility to end-organ kidney damage (2,9,10,12,24). While the genes responsible for development of hypertensive renal disease have not been elucidated, the pathological changes that typically occur represent an arteriolopathic process, and it is logical to hypothesize that the responsible genetic alterations affect the renal vascular response to hypertension.…”
mentioning
confidence: 99%